EGFRvIII deletion mutations in pediatric high-grade glioma and response to targeted therapy in pediatric glioma cell lines - Bax, Dorine A. (2009)
Purpose: The epidermal growth factor receptor (EGFR) is amplified and overexpressed in adult glioblastoma, with response to targeted inhibition dependent on the underlying biology of the disease. EGFR has thus far been considered to play a less important role in pediatric glioma, although extensive data are lacking. We have sought to clarify the role of EGFR in pediatric high-grade glioma (HGG). Experimental Design: We retrospectively studied a total of 90 archival pediatric HGG specimens for EGFR protein overexpression, gene amplification, and mutation and assessed the in vitro sensitivity of pediatric glioma cell line models to the small-molecule EGFR inhibitor erlotinib. Results: Amplification was detected in 11% of cases, with corresponding overexpression of the receptor. No kinase or extracellular domain mutations were observed; however, 6 of 35 (17%) cases harbored the EGFRvIII deletion, including two anaplastic oligodendrogliomas and a gliosarcoma overexpressing EGFRvIII in the absence of gene amplification and coexpressing platelet-derived growth factor receptor α. Pediatric glioblastoma cells transduced with wild-type or deletion mutant EGFRvIII were not rendered more sensitive to erlotinib despite expressing wild-type PTEN. Phosphorylated receptor tyrosine kinase profiling showed a specific activation of platelet-derived growth factor receptor α/β in EGFRvIII-transduced pediatric glioblastoma cells, and targeted coinhibition with erlotinib and imatinib leads to enhanced efficacy in this model. Conclusions: These data identify an elevated frequency of EGFR gene amplification and EGFRvIII mutation in pediatric HGG than previously recognized and show the likely necessity of targeting multiple genetic alterations in the tumors of these children.